PENINGKATAN KETERAMPILAN MENULIS NASKAH DRAMA DENGAN MENGGUNAKAN MEDIA SHORT FILM PADA PESERTA KELAS VIII DI SMP NEGERI 3 JOMBANG TAHUN PELAJARAN 2018/2019 - Ali Nuke Affandi (SASTRANESIA: Jurnal Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2019)
Students think that writing skill is difficult because students determine to be difficult to convey their thoughts, ideas, or opinions into a piece of writing. To deal with this problem, it is very necessary to have a media to facilitate students to convey thoughts, ideas, or opinions into a writing. The lack of instructional media used by teachers in the teaching and learning process also causes a sense of laziness and limited ideas on students to take a theme and make it to a complete drama script. This study aims to improve students’ writing skill of drama scripts for VIII B students at SMPN 3 Jombang by using instructional media in the form of short film. Learning by using the short film as media is a mean for teaching writing drama scripts by utilizing listening activities and writing important things  in the film being watched. Then this activity is developed into drama scripts according to the elements, structure and rules of drama.The research method used in this study is a classroom action research conducted for two cycles, namely cycle I and cycle II. Each cycle has four steps including planning, implementing, observing and reflecting. This research uses analysis techniques in the form of qualitative descriptive analysis.Based on the result of the study, the use of Short Film as a media improve the students’ writing skill of drama scripts in the eighth grade students of SMPN 3 Jombang. The media has improved students’ writing skill at each stage of the cycle, this can be seen from the improvement in the average value of students during pre-cycle, cycle I and cycle II. In the pre-cycle stage, the average value of students gets 66.75. In the first cycle, it has increased the average value to 73.25 and in the second cycle, it has also increased to 84.5.